Characterization of air to fuel ratio control and non-selective catalytic reduction on an integral compressor engine - Wolfram, Kyle Martin (Kansas State University, 2008)
In the natural gas production industry, recent legislation has mandated new emission regulations for low horsepower reciprocating internal combustion engines. One method to achieve compliance of the new regulations is the use of non-selective catalytic reduction. Nonselective catalytic reduction utilizes a three-way catalyst and an air-to-fuel ratio controller to oxidize carbon monoxide and unburned fuel while reducing oxides of nitrogen. Testing of a non-selective catalytic reduction system was preformed on a typical exploration and production engine, a Compressco GasJack. To fully test the unit, exhaust gas samples were taken with an ECOM gas analyzer both before and after the catalyst over typical engine speeds and powers. By sampling the exhaust gas concentration before and after the catalyst, the catalyst efficiency or percent reduction in exhaust gas specific concentrations were calculated. Additionally by testing throughout the engine's typical operation range, conditions under which the non-selective catalyst reduction system fails were determined. After testing, it was found that the three-way catalyst was effective at reducing oxides of nitrogen by 98% at all speeds and power conditions. Carbon monoxide was reduced by 90% under all conditions except for maximum speed and power. At maximum speed and power, the conversion efficiency for carbon monoxide was recorded as low as 32%. One reason for the low conversion efficiency at maximum speed and power was that the oxygen concentration entering the catalyst was not sufficient to oxidize the carbon monoxide to carbon dioxide. These results indicate the three-way catalyst was effective at reducing emissions when the controller correctly maintained the pre-catalyst oxygen concentration. However, the controller was unable to maintain engine operation at the ideal airto- fuel ratio at all test conditions. The controller failed to keep the pre-catalyst oxygen concentration in the correct range because the oxygen sensor was not accurate and consistent in its output. Future work on the development of a more robust oxygen sensor is recommended.
Keywords: NSCR; AFRC; Catalyst; Engine; Non-Selective; Catalytic; Engineering, Mechanical (0548)